SW-Blend: Student worksheets for blended learning based on case-based learning model - Euis Winarti; Noerlina Anggraeni; Rika Sa'diyah; Lufty Hari Susanto; Ilmi Zajuli Ichsan; Sri Nurafifah (Research and Development in Education (RaDEn), 2024)
Blended learning is learning that is a mixture of online and offline in class that must improve with innovation. Blended learning can be implemented using various learning tools that are integrated with learning models, one of which is the case-based learning model. This research aims to develop student worksheets for blended learning (SW-Blend) based on the case-based learning model. The method used in this research is research and development (R&D) with an approach using the ADDIE development stages. The implementation of this research will be in future research. The results of this research are that according to the results of the initial analysis, 90% of respondents have used a learning management system, 38.57% have not used problem-based student worksheets, and 42.57% still rarely use case-based learning. The validation results of the SW-Blend that have been developed are categorized as very valid so they are suitable for use in learning. Learning using blended learning is very important to be implemented using learning tools, in this case, SW-Blend based on case-based learning to improve students' critical thinking skills.